Evaluasi Program Penguatan Perempuan Usaha Kecil (PUK) (Evaluasi Sumatif Terhadap Program Penguatan PUK Yang Dilakukan Asosiasi Pendamping Perempuan Usaha Kecil Di Solo) - Cahyanto, Agung; Rahayu, Ety (UI Scholars Hub, 2015)
This research is a study summative evaluation PUK Strengthening Program in Solo with a quantitative approach. The goal is to measure outcome indicators and analyzes the factors that influence the achievement of outcomes based on aspects of the process and input. The analysis was done by means of univariate and bivariate with cross table, Chi Square and Kendall Tau. The results showed that the outcome indicators has not been achieved. Factors that influence the outcome of the process aspect are ability to identify and solve problems, quality of production, volume of business, business innovation, profit exhibitions, as well as participation in training. Input factors affecting outcome that is age and education of respondents